Innovations in Infrastructure Proceedings of ICIIF 2018 - Deb, Dipankar; Balas, Valentina E.; Dey, Rajeeb; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book covers innovative research and its applications in infrastructure development and related areas. This book discusses the state-of-art development, challenges and unsolved problems in the field of infrastructure/smart development, control engineering, power system infrastructure, smart infrastructure, waste management and renewable energy. The solutions discussed in this book encourage the researchers and IT professionals to put the methods into their practice.
Innovation in Telecommunication Infrastructure -- Innovation in Control Engineering -- Innovation in Power system Infrastructure -- Innovation in Smart Infrastructure -- Innovation in Waste Management -- Sustainable Solutions for Infrastructure Development -- Innovation in Thermal Engineering -- Innovation in Manufacturing -- Innovation in Industrial Infrastructure -- Innovation in Renewable Energy -- Innovation in Hybrid Vehicles -- New Optimization Techniques -- Innovation in Mechatronics -- Innovation in Machine Learning -- Innovation in Indigenous and Rural technologies.
Keywords: Telecommunication; Control engineering; Renewable energy sources; Technological innovations; Electric power production; Refuse and refuse disposal; Communications Engineering, Networks; Control and Systems Theory; Renewable Energy; Innovation and Technology Management; Electrical Power Engineering; Waste Management/Waste Technology